ANALISIS KONSEPTUAL BIMBINGAN DAN PENYULUHAN DALAM PERSPEKTIF PENDIDIKAN ISLAM - Amelia Khoirunisa; Dinda Kenanga Larasati; Nirena Zahra Melia S.; Wiwin Luqna Hunaida (Qolamuna : Jurnal Studi Islam, 2025)
Education not only aims to develop academic skills, but also to shape the character and spirituality of learners. In the context of Islamic education, guidance and counseling are important components that support the holistic development of learners, including intellectual, spiritual, and moral aspects. This article analyzes the concept of guidance and counseling based on the principles of Islamic education, focusing on individual, group, thematic, and problem-based approaches. This research uses a literature study method with content analysis to explore the principles and practices of Islamic guidance. The results show the importance of integrating Islamic values into the curriculum, continuous counselor training, and cooperation between counselors, teachers and parents. Despite facing challenges such as limited resources and changing social dynamics, this approach remains relevant to help learners develop their potential optimally in various aspects of life. Keywords : Guidance and Counseling, Islamic Education, Islamic Guidance